The effects of bagging on fresh fruit quality of Canarium album - Zhou, Junhui; Zhong, Guofeng; Lin, Zhuozhen; Xu, Hui-lian; Mathooko, F. M (Orgz, 2010)
The effects of bagging with different bags to the clusters on fresh fruit quality in Xiangtian olive of Canarium album were studied. The results indicated that, the color and smoothness were better, the edible pulp rate and ascorbic acid concentration were higher after bagging than in the control during the two years’ experiments, but the fruit soluble solids were decreased. It showed that the golden yellow color, more smoothness, higher single fruit weight, more delicate flesh and better degree of slag for the fruits were obtained with Shengda double-layer bags especially. However, the bags need size specifications modified with few holes on the bottom.
Keywords: Xiangtian olive; Fruit bagging; Fresh fruit quality; Canarium album